EFEKTIVITAS INTERVENSI SLEEPWELL BERBASIS AROMATERAPI DAN SLEEP JOURNAL REFLEKTIF TERHADAP GEJALA INSOMNIA PADA MAHASISWA - Susanti, Ruth Natalia; Ilda Putri Febrianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Insomnia is a common health problem among university students and has significant impacts on cognitive functioning, emotional regulation, and academic performance. The management of insomnia is still predominantly focused on pharmacological interventions, which may carry potential side effects; therefore, safe and easily applicable non-pharmacological alternatives are needed. This study aimed to examine the effectiveness of the SleepWell intervention based on lemongrass aromatherapy and a reflective sleep journal in reducing insomnia symptoms among university students. The study employed an experimental pretest–posttest control group design. A total of 10 students with poor sleep quality based on the Pittsburgh Sleep Quality Index (PSQI) were randomly assigned to an intervention group (n = 5) and a control group (n = 5). The intervention group received a lemongrass aromatherapy bracelet and completed a reflective sleep journal for 10 consecutive days, while the control group received no intervention. The results showed that the intervention group demonstrated a greater reduction in mean PSQI scores, decreasing from 12.6 to 8.4, whereas the control group exhibited only fluctuating changes from 15.2 to 13.6. Improvements in the intervention group were primarily observed in sleep latency, subjective sleep quality, sleep efficiency, and daytime dysfunction, although individual responses varied. These findings indicate that the SleepWell intervention has the potential to serve as a simple and applicable non-pharmacological approach to reducing insomnia symptoms among university students. Further studies with larger sample sizes and longer intervention durations are recommended to strengthen these findings.